Modeling the Downstream Processing of Monoclonal Antibodies Reveals Cost Advantages for Continuous Methods for a Broad Range of Manufacturing Scales. Issue 2 (9th February 2018) - Hummel, Jonathan; Pagkaliwangan, Mark; Gjoka, Xhorxhi; Davidovits, Terence; Stock, Rick; Ransohoff, Thomas; Gantier, Rene; Schofield, Mark
Abstract : The biopharmaceutical industry is evolving in response to changing market conditions, including increasing competition and growing pressures to reduce costs. Single‐use (SU) technologies and continuous bioprocessing have attracted attention as potential facilitators of cost‐optimized manufacturing for monoclonal antibodies. While disposable bioprocessing has been adopted at many scales of manufacturing, continuous bioprocessing has yet to reach the same level of implementation. In this study, the cost of goods of Pall Life Science's integrated, continuous bioprocessing (ICB) platform is modeled, along with that of purification processes in stainless‐steel and SU batch formats. All three models include costs associated with downstream processing only. Evaluation of the models across a broad range of clinical and commercial scenarios reveal that the cost savings gained by switching from stainless‐steel to SU batch processing are often amplified by continuous operation. The continuous platform exhibits the lowest cost of goods across 78% of all scenarios modeled here, with the SU batch process having the lowest costs in the rest of the cases. The relative savings demonstrated by the continuous process are greatest at the highest feed titers and volumes. These findings indicate that existing and imminent continuous technologies and equipment can become key enablers for more cost effective manufacturing of biopharmaceuticals. Abstract : Continuous bioprocessing technologies have attracted interest as potential enablers of cost effective drug manufacturing for quite some time. However, uncertainties around the specific cost benefits, as well as limited availability of continuous solutions at certain scales, have prevented adoption for most manufacturers. Is it possible that existing and upcoming continuous technologies are catching up with the needs of manufacturers? Thorough cost modeling studies can help when attempting to answer this question.